Hunting by the Stroke: How Foraging Drives Diving Behavior and Locomotion of East-Greenland Narwhals (Monodon monoceros) - Tervo, Outi M.; Ditlevsen, Susanne; Ngô, Manh C.; Nielsen, Nynne H.; Blackwell, Susanna B.; Williams, Terrie M.; Heide-Jørgensen, Mads Peter (Frontiers in Marine Science, 2021)
Deep diving air-breathing species by necessity must balance submergence time and level of exercise during breath-holding: a low activity level preserves oxygen stores and allows longer duration submergence whereas high activity levels consume oxygen quickly and shorten submergence time. In this study, we combined high-resolution multi sensor animal-borne tag data to investigate diving behavior and locomotion styles of the narwhal (Monodon monoceros) (n=13, mean record length 91 h) - a deep diving Arctic species. Narwhals in this study dove down to >800 m but despite the deep diving abilities, one-third of the dives (33%) were shallow (> 100 m) and short in duration (< 5 min). Narwhals utilized energy saving measures such as prolonged gliding during descent with increasing target depth but stroked actively throughout the ascent indicating excess oxygen storages. Foraging behavior, as detected by the presence of buzzes, was a key factor influencing dive depth and spinning behavior – the rolling movement of the animal along its longitudinal axes. Narwhals in East Greenland utilized two foraging strategies, while transiting and while stationary, with different target depths and buzzing rates. The first targeted deep-dwelling, possibly solitary prey items and the latter, more schooling prey closer to the surface. The buzzing rate during stationary foraging was on average twice as high as during transiting foraging. Spinning was an integrated part of narwhal swimming behavior but the amount of spinning was correlated with foraging behavior. The odds for spinning during all dive phases were 2-3 times higher during foraging than non-foraging. Due to the spinning behavior, stroking rate might be better suited for estimating energy consumption in narwhals than ODBA (Overall dynamic body acceleration). The narwhal is considered as one of the most sensitive species to climate change - the results from this study can act as a baseline essential for evaluating changes in the behavior and energy usage of narwhals caused by stressors evolving in the Arctic.